Foundations of Organizational Behavior : An Applied Perspective - Bélanger, Laurent (Relations Industrielles / Industrial Relations, 1984)
This article reviews the book, "Foundations of Organizational Behavior : An Applied Perspective," by Andrew J. Dubrin.